Evaluation Of Sugarcane (Sacccharum Officinarum L.) Mid-Late Clones Under Waterlogging Conditions Of Bihar (India) (Applied Biological Research, 2018)
Yield and juice quality of 16 sugarcane clones, procured from Sugarcane  Research Institute, DRPCAU, Pusa, Samastipur, Bihar (India), was evaluated  under waterlogging stress condition during 2016 to 2017. The trials were laid  out in a randomized block design with three replications. The depth of water  was 130 cm for 15 days of August. The experimental plot remained  waterlogged during June-September 2016 varied from 30 to 90 cm. Three  budded sets from upper half of the canes were used for planting. Planting was  done following full agronomic and plant protection practices recommended  for North Bihar (India) conditions. The result revealed high heritability  coupled with high genetic advance, as per cent of means, for cane yield, leaf area  index at 30 days after waterlogging, leaf area index before waterlogging, leaf  area index at 60 days after waterlogging and sugar yield suggesting the  preponderance of additive genetic effect in the determination of these traits. It  also indicated that selection for these traits will be effective if desired  improvement is to bring for cane and sugar yield under waterlogged condition.  Ranking of clones based on selection index and three other criteria revealed  that clone CoP2061 was the most suitable clone among the clones studied. The  clone can directly be used as varieties for waterlogging tolerance and may be  used in crossing programme as parents to develop waterlogging tolerant clone.
Keywords: Rank correlation; selection indices; sugarcane; waterlogged tolerance